Low-grade squamous intraepithelial lesion: therapeutic and pathogenic properties of activated glycyrrhizinic acid - Borovikov I.O; Kutsenko I.I; H.I. Gorring; E.R. Rubinina; V.P. Bulgakova (LCC «Medicine-Inform», 2019)
I.O. Borovikov1, I.I. Kutsenko1, H.I. Gorring1, E.R. Rubinina1, V.P. Bulgakova1,2 1Kuban State Medical University, Krasnodar, Russian Federation 2LLC "Clinic Ekaterininskaya", Krasnodar, Russian Federation Background: the importance of human papilloma virus (HPV) prevalence is accounted for by HPV malignancy including cervical cancer. Cervical cancer is the fourth most commonly occurring cancer in women and the seventh most commonly occurring cancer overall. The lack of effective preventive, screening, and treatment strategies for precancerous cervical lesions (i.e., squamous intraepithelial lesions) is the major cause of high cervical cancer prevalence. Aim: to assess the efficacy of local treatment with activated glycyrrhizinic acid (0.1% spray) in women with low-grade squamous intraepithelial lesion (LSIL). Patients and Methods: 76 women who received were enrolled. Clinical examination as well as colposcopy, cytohistology, and cytobiochemistry were performed. LSIL diagnosis was verified by clinical microbiological and cytological studies (fluid cytology). Infection with high-risk HPV was verified by PCR for the detection of 12 high-risk HPV types. Oxidative processes  in cervical mucosa were assessed by measuring NO, reactive oxygen species, and lipids. Macrophage enzyme activity was evaluated by myeloperoxidase, acidic phosphatase, and non-specific esterase. 30 healthy women were cytobiochemical controls. Results: 85.5% and 90.8% of women with LSIL had a normal colposcopy in 30 days and a year, respectively, after the treatment with activated glycyrrhizinic acid. No koilocytotic atypia was revealed in 81.6% and 89.5% of women in 30 days and a year, respectively, after the treatment. The treatment has also resulted in the changes in cervical oxidation processes, i.e., electron paramagnetic resonance (EPR) signal intensity of lipid peroxyl radicals has reduced by 3.8 times and NO by 2.4 times while EPR signals of O2 were almost undetectable. As to cervical macrophage enzymes, the activity of myeloperoxidase and acidic phosphatase has increased by 54.4±5.9% and 63.9±6.4%, respectively, while the activity of non-specific esterase has increased more than twice. Conclusion: high clinical efficacy of the local treatment with activated glycyrrhizinic acid for LSIL (which have resulted in the normalization of immune and oxidation processes in the cervix) was demonstrated. Keywords: human papilloma virus, squamous intraepithelial lesion, glycyrrhizinic acid. For citation: Borovikov I.O., Kutsenko I.I., Gorring H.I. et al. Low-grade squamous intraepithelial lesion: therapeutic and pathogenic properties of activated glycyrrhizinic acid. Russian Journal of Woman and Child Health. 2019;2(4):301-305.